Coming climate crisis? consider the past, beware the big fix - Parkinson, Claire L. (Why of where., 2010)
Decisively cutting through the hyperbole on both sides of the debate, the author, a distinguished NASA climatologist brings much needed balance and perspective to the highly contentious issue of climate change. Offering a knowledgeable overview of global conditions past and present, she lays out a compelling argument that our understandings and models are inadequate for confident predictions of the intended and unintended consequences of various projects now under consideration to modify future climate. In this work, she presents a coherent synopsis of the 4.6 billion year history of climate change on planet Earth, both before and after humans became a significant factor, and explores current concerns regarding continued global warming and its possible consequences. She ranges over the massive geoengineering schemes being proposed and why we need to be cautious about them, the limitations of current global climate models and projections, the key arguments made by those skeptical of the mainstream views, and the realistic ways we can lessen destructive human impacts on our planet. While discussing all of these polarizing topics, the author consistently shows respect for the views of alarmists, skeptics, and the vast majority of people whose positions lie somewhere between those two extremes. The book clarifies some of the most contentious points in the climate debate, and in the process treats us to a discussion interweaving Earth history, science, the history of science, and human nature.